(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Mithya-ahara vihara is a causative factor leading to become a diabetic. Ayurveda, a science of life, take forward to human being to live healthy. Complications of uncontrolled diabetes mellites (DM) presents with micro and macro vascular changes, atherosclerosis, developing progressive neuropathy, and ischemia in specifically lower limbs. In diabetic patients, regular and proper foot care is an important one. Neuropathic changes may result in formation of ulcers, it may be due to repeated injuries. Presence of infection may hamper in healing of ulcer. These factors inherited to become chronic or non-healing type. Prevention of ulcer can be done with medications and regular dressing. In Ayurveda, non-healing ulcer can be resembled with Dusta Vrana. Assessment of Dosha prakopa decides to which Vrana Chikitsa upakram (treatment plans) is to be implicated. On the basis of Ayurved chikitsa siddhanta, an attempt is made to treat a case of Dusta vrana. A 55 years old male patient presented with ulcers in left foot with pain, swelling, pus discharge for 6 months. On the basis of Lakshans and Dosha assessment (sign and symptoms), he was diagnosed as Madhumehajanya dusta vrana. This patient was treated successfully with Jalokavacharana (leech Application) followed by indigenous drugs. After 6 months of regular treatment, ulcers were completely healed.